A scholarly approach to student success in Higher Education Volume 2: transformative pedagogies - Pool, J; Fernandes-Martins, MM; Fourie, M (My University, 2022)
A Scholarly Approach to Student Success in Higher Education Volume 2 is a research book based on original research in the field of Higher Education enhancing theory and practice. The overarching theme for this publication relates to higher education pedagogic best practices. The chapters encapsulate empirical and conceptual research guided by theoretical frameworks. This scientifically-based publication is underpinned by the underlying approaches for the advancement of scholarship in higher education. The contribution of the book offers original research. The content is aimed at academics as university teachers in the field of scholarship of teaching and learning. The work of an academic involves being a teacher and a researcher; teaching must be researchinformed. Good teaching is grounded in a deep understanding of a discipline: the basis of academics’ work is knowledge, with their identities embedded in disciplineas knowledge learners, producers and disseminators. This publication places emphasis on transformative curricula and pedagogies applicable to enhancing quality teaching and learning informed by a scholarly approach towards student success, as envision by the Department of Higher Education and Training (DHET) of South Africa. A Scholarly Approach to Student Success in Higher Education Vol 2 fosters a space for academics to share developed learning and teaching practices and research toward student success. There are chapters that address the clear inequalities that persist in HE and building quality towards student access with success. Curriculum responsiveness pertaining to decolonisation, sustainable development and climate change, and the need for entrepreneurship development is also evident in the chapters. A Call for Chapters was announced using different channels such as Higher Education Learning and Teaching Association of Southern Africa (HELTASA) News and various inter-university communication platforms. A substantial number of manuscripts were submitted by local, national and international scholars. Under the auspices of the editors, assisted by selected national and international members of the editorial board, all of the manuscripts were scrutinised. Those manuscripts that did apply to the standards and foci set for publication, went through a double-blind peer-review as well as an authentication process in order to secure the fact that the content was not plagiarised. An academic integrity specialist was appointed to analyse TurnItIn reports. Chapters were also language edited and corrections were made by the authors accompanied by a change-log which was screened by the editors. In cases where a discrepancy of the outcome from reviewers was reported, the chapter was submitted to a scholar of standing in the field in order for him/her to act as an arbiter to make a final decision regarding the merits of a particular chapter. All of the reports are currently preserved in the offices of the publisher. A Scholarly Approach to Student Success in Higher Education Volume 2 adds to the established body of knowledge on the scholarship of teaching in Higher Education in South Africa. The relevance, nature, and novelty of this book publication is seated in its contribution to a scholarly approach to student success